Stone Formation from Nonabsorbable Clip Migration into the Collecting System after Robot-Assisted Partial Nephrectomy - Ziho Lee; Christopher E. Reilly; Blake W. Moore; Jack H. Mydlo; David I. Lee; Daniel D. Eun (Case Reports in Urology)
We describe a case in which a Weck Hem-o-lok clip (Teleflex, Research Triangle Park, USA) migrated into the collecting system and acted as a nidus for stone formation in a patient after robot-assisted partial nephrectomy. The patient presented 2 years postoperatively with left-sided renal colic. Abdominal computed tomography scan showed a 10 millimeter renal calculus in the left middle pole. After using laser lithotripsy to fragment the overlying renal stone, a Weck Hem-o-lok clip was found to be embedded in the collecting system. A laser fiber through a flexible ureteroscope was used to successfully dislodge the clip from the renal parenchyma, and a stone basket was used to extract the clip.